Providing a structural model of psychological well-being prediction based on family functioning, optimism, and resilience mediated by social adequacy - Lotfnejadafshar, Sima; Khakpour, Reza; Dokanehi Fard, Farideh (Applied Family Therapy Journal (AFTJ), 2022)
Aim: This study was conducted to provide a structural model of psychological well-being prediction based on family functioning, optimism, and resilience mediated by social adequacy. Methods: This was a descriptive correlational study with structural equation modeling (SEM). The statistical population included students of Allameh Tabatabaei Campus in Urmia (for sisters) and Shahid Rajaei Campus in Urmia (for brothers) from which 250 people were selected as the sample by convenient sampling method. The study tools were Ryff's (1989) Psychological Well-Being Scales (PWB), McMaster's (1950) Family Assessment Device (FAD), Scheier and Carver's (1985) Life Orientation Test (LOT), Connor-Davidson (2003) Resilience scale (CD-RISC), and Flanner et al.'s (1990) Social Adequacy Scale. Results: The findings suggested that there was a positive relationship between resilience and psychological well-being (p